Intraoperative Mother and Baby Skin-to-Skin Contact during Cesarean Birth: Systematic Review. Issue 5 (September 2020) - Frederick, Anitra; Fry, Tena; Clowtis, Licia
Abstract: Purpose: Experts recommend immediate skin-to-skin (SSC) contact for all alert and stable mothers and newborns after birth. Clinicians are working to incorporate immediate (intraoperative) SSC during cesarean birth. The purpose of this systematic review is to describe the state of the science of intraoperative SSC for mother and baby and increase clinician's awareness of its potential benefits and risks. Study Design and Methods: A systematic approach was followed throughout the review process. CINAHL, PubMed, and Embase databases were searched using strategies constructed by an academic health sciences librarian. Articles included in the review focused on SSC initiated during cesarean birth. Results: Thirteen studies were selected for the mixed-method systematic review. Six prospective studies, four retrospective chart reviews, and three qualitative studies met the inclusion criteria. Maternal stress levels were reduced, whereas comfort, oxytocin, and antioxidant levels increased with intraoperative SSC. Physiologic measures of successful newborn transition showed little difference between newborns held in intraoperative SSC and those who were not. Synthesis of qualitative experiences revealed mothers' intense desire to hold and know their baby immediately after birth. Clinical Implications: Intraoperative SSC is a safe, beneficial, and highly desirable practice for mothers and newborns experiencing cesarean birth. Although barriers exist to its implementation, nurses can facilitate and support this practice. Evidence-based, family-centered intraoperative SSC should be offered to all stable mothers and babies according to recommendations and in a manner that promotes safe outcomes, including following current nurse staffing guidelines. Abstract : Placing the newborn skin-to-skin on the mother's chest after birth while cesarean surgery is completed was found to be beneficial in this systematic review. Safety of mother and baby during skin-to-skin contact are promoted when nurse staffing in the operating room and post anesthesia care unit are consistent with published professional guidelines so the mother-baby couplet can be continually assessed.